Gambaran Status Gizi dan Pola Makan Ibu Menyusui di Kelurahan Benu-Benua Kecamatan Kendari Barat Tahun 2024 - Erin Landepasa; Devi Savitri Effendy; Febriana Muchtar (Jurnal Kendari Kesehatan Masyarakat, 2025)
Nutritional status is a condition caused by a balance between the intake of nutrients needed for body metabolism. This study aims to determine the nutritional status and dietery patterns of breastfeeding mothers. This type of research uses a quantitative descriptive survey with a cross sectional approach. The population in this study were all breastfeeding mothers in Benu-Benua Village, district west Kendari. The prevalence of chronic energy deficiency (CED) based on Upper Arm Circumference (LLA) in breastfeeding mothers in Benu-Benua Village it is 11.9%. Energy intake in Benu-Benua Village is predominantly normal, while protein, fat and carbohydrate intake is predominantly deficit or deficient. Food diversity for Benu-Benua Village found that they predominantly consumed food that was not diverse. The food frequency for Benu-Benua Village predominantly has a good main meal frequency, namely ≥3 times a day